Poder de mercado no varejo de etanol no estado de São Paulo - Santos, Jaqueline Zani dos (Universidade Federal de São Carlos, 2012)
Given the economic dimension of the sugar and ethanol industry, there is a strong concern regarding the loss of social welfare due to market power usage by ethanol companies, especially at retail, where conditions are favorable to cooperation. The present study's objective is to determine if there is any market power abuse in retail sales of hydrous ethanol in the State of São Paulo, by verifying if price increases and decreases are transmitted to the customer proportionally, and identifying if there is any difference in price transmission mechanisms between smaller (where competition is less) and larger tows. Monthly wholesale and retail price series are used, provided by ANP, for the period of January 2005 to August 2011, for a sample of cities in the state of São Paulo. The results indicated that market power was used in the ethanol retail market, where retailers were able to transmit to the consumers price increases faster than decreases.
Keywords: economia de mercado; mercado combustível São Paulo (Estado); organização industrial; poder de mercado; transmissão de preços; varejo; etanol; market power; price transmission; retail; ethanol; CIENCIAS SOCIAIS APLICADAS::ECONOMIA